Economic security of enterprises as a factor of success of modern business - Kovtun , A. (Ways to Improve Construction Efficiency, 2023)
The article examines the problem of ensuring the economic security of construction enterprises in the current conditions of an unstable economic environment, in particular under the influence of the crisis caused by the war, digitalization and modernization of enterprises. The main aspects of economic security are outlined, including financial stability, the ability of enterprises to counteract internal and external threats, as well as the effectiveness of risk management. The article analyzes scientific approaches to determining the economic security of enterprises, which consider it as a state of protection of critically important processes from external and internal threats. The main threats to the economic security of enterprises are identified, including unfair competition, instability of the external environment, the risk of raider seizures and financial threats associated with the instability of income and expenses. Approaches to the formation of a reliable economic security system are proposed, which provides for a set of measures of an economic, legal, organizational and information and technological nature, focuses on the importance of integrating digital technologies into the process of managing the economic security of construction enterprises. The issue of adapting international financial reporting standards as one of the key factors in increasing the level of financial stability and investment attractiveness of companies is considered. The role of financial and economic security in ensuring the competitiveness of construction enterprises in the long term is especially emphasized. It is concluded that effective management of the economic security of enterprises requires the implementation of monitoring and risk analysis tools, as well as the formation of rapid response mechanisms to potential threats. It is determined that security measures must be balanced in order to avoid excessive costs for their implementation. The study substantiates the need to develop a comprehensive strategy for the economic security of construction enterprises, which takes into account modern challenges and threats.